Structure, mechanical characteristics and in vitro degradation, cytotoxicity, genotoxicity and mutagenicity of novel biodegradable Zn-Mg alloys - Kubásek, J; Vojtěch, D; Jablonská, E; Pospíšilová, I; Lipov, J; Ruml, T (Materials science & engineering. C, Materials for biological applications, 2016)
Zn-(0-1.6)Mg (in wt.%) alloys were prepared by hot extrusion at 300 °C. The structure, mechanical properties and in vitro biocompatibility of the alloys were investigated. The hot-extruded magnesium-based WE43 alloy was used as a control. Mechanical properties were evaluated by hardness, compressive and tensile testing. The cytotoxicity, genotoxicity (comet assay) and mutagenicity (Ames test) of the alloy extracts and ZnCl2 solutions were evaluated with the use of murine fibroblasts L929 and human osteosarcoma cell line U-2 OS. The microstructure of the Zn alloys consisted of recrystallized Zn grains of 12 μm in size and fine Mg2Zn11 particles arranged parallel to the hot extrusion direction. Mechanical tests revealed that the hardness and strength increased with increasing Mg concentration. The Zn-0.8 Mg alloys showed the best combination of tensile mechanical properties (tensile yield strength of 203 MPa, ultimate tensile strength of 301 MPa and elongation of 15%). At higher Mg concentrations the plasticity of Zn-Mg alloys was deteriorated. Cytotoxicity tests with alloy extracts and ZnCl2 solutions proved the maximum safe Zn(2+) concentrations of 120 μM and 80 μM for the U-2 OS and L929 cell lines, respectively. Ames test with extracts of alloys indicated that the extracts were not mutagenic. The comet assay demonstrated that 1-day extracts of alloys were not genotoxic for U-2 OS and L929 cell lines after 1-day incubation.
Keywords: In vitro testing; poškození DNA; viabilita buněk; DNA Damage; Cell Line, Tumor; Cell Survival; hořčík; Mechanical properties; slitiny; Magnesium; kultivované buňky; Alloys; Animals; lidé; biokompatibilní materiály; Cytotoxicity; Humans; zvířata; Genotoxicity; myši; zinek; Cells, Cultured; nádorové buněčné linie; Mice; Zinc; Biocompatible Materials